Analytical study of demand and supply in teacher labour market of Kerala state - Noufal Farook, P (Department of Education, University of Calicut, 2025)
Educational Economics is an important field of study which is lacking much research endeavours. Teacher labour market is one of the major labour market in India with a significant percentage of labour devoted to the various educational institutions in each state. Aim of the study was a comprehensive analysis of the structure of teacher labour market of Kerala state, trend of demand and supply and influencing factors. The study was qualitative in nature and included three phases: 1. Preliminary Interview, 2. Document Analysis and 3. Phase of survey and interview. Investigator collected documents from District Educational Offices, Kerala Public Service Commission and published and unpublished government documents for document analysis. Interviews and surveys were also conducted to collect data from teachers working in schools at Lower Primary, Upper Primary and High School levels and principals of unaided schools. The number of teachers taken as sample was 220. Analysis of Kerala's teacher labour market showed distinct patterns in school distribution, teacher demographics, and employment trends across various sectors. The aided schools dominate the school education in the state. According to teacher demographics, male teachers are comparatively more in numbers in high schools, but female teachers dominate the sector, particularly in Lower Primary and Upper Primary schools. The supply of teachers consistently exceeded demand in all districts and all years, which indicates a persistent oversupply in Kerala's teacher labour market. Internal dynamics, particularly teacher transfers, retirements, and promotions, emerge as primary factors influencing teacher demand in government and aided schools. Among the factors influencing supply, non-monetary factors such as the status of the teaching profession, occupational choices, and support from management and colleagues significantly impact supply of teachers. Continued investment in recruitment, professional development, and resource allocation is crucial for strengthening government school workforce. The surplus of teachers brings about an opportunity to upskill the teaching workforce.
Keywords: Teacher demand; Teacher Supply; Teacher Labour Market; Teacher Employment; Teacher Recruitment; Educational Manpower Planning.